OVERVIEW OF STRUCTURE AND PROGRESS ON ROMANIAN SWINE SECTOR IN THE E.U. CONTEXT - Niţescu, Crstina (Economics of Agriculture, 2011)
Summary analysis of theoretical and operational issues regarding the economic organization and operation of swine breeding holdings highlights a general conclusion regarding the need to address it as a cybernetic system where all the components have linear and non-linear relations among one another. The evolution of this dynamic system is often unpredictable and diffcult to assess. Thus, previous actions underlying the present which, in turn, prefgure future trajectories of organizations on the principles of reverse connection. Therefore, in each such economic organization several impact factors have major impact on the systems stability and order. The EU context, in terms of structure of agricultural holdings, namely the swine breeding farms, has significant impact on the Romanian animal breeding farms, small, medium and large size one, which have to deal with the actual market competition (local and international) in order to integrate successfully within the community structures.